Organic Fertilizer for Rubber Trees: Implementation of Empowerment Program for Rubber Farmers in Pagar Dewa Village: Implementation of Empowerment Program for Rubber Farmers in Pagar Dewa Village - Gokhan; Adi Martono; Lukas Raditya; Muhammad Raushan Fikri (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
Pagar Dewa Village is located in Lubai Ulu District, Muara Enim Regency, South Sumatra Province, with vast natural potential for rubber plantations. In line with this condition, the majority of the community in Pagar Dewa Village works as rubber farmers. However, the potential has not been fully realized to its maximum benefit by the rubber farmers in Pagar Dewa Village. Various issues are faced by rubber farmers, ranging from the increase in non-subsidized fertilizer prices, the absence of fertilization for the past three years, limited information available to rubber farmers, to the threat of forest and land fires. In response to these issues, PT Perusahaan Gas Negara Tbk - Pagardewa Gas Compressor Station, through its CSR program, has implemented a community empowerment program based on rubber farmers. The program, titled "Self-Reliant, Alert, Resilient, and Prosperous Rubber Farmers" (MAS TANI MAPAN), began by reviving the farmer cooperative that had experienced a non-active phase and assisting in managing the institution. It also developed the cooperative into fertilizer, seed, and honey working groups (Pokja Pupuk, Pokja Bibit, and Pokja Madu). This program also enhances the capacity of rubber farmers through training in seedling cultivation and organic fertilizer production for rubber trees.